Hidden Threats, Preventive Efforts, and Resolving Non- Communicable Diseases among Soldiers in Nepal (The Shivapuri Journal, 2026)
Non-communicable diseases (NCDs) represent an unrecognized threat to military personnel, causing premature mortality and disability. Previous research showed that NCDs in the Nepali Army include cardiovascular diseases, diabetes, mental health disorders, and exertional heat-related illness. Risk factors are linked to modifiable lifestyle behaviors and military service-related exposures. Studies reveal alarming prevalence rates: 13.4% hypertension, 25.27% major depression, and increasing metabolic disorders among serving soldiers. NCDs compromise operational readiness, increase medical costs, and impact the overall welfare of soldiers. Interventions targeting behavioral changes and comprehensive prevention strategies are critical. This research employs a mixed-method approach incorporating the research analysis of qualitative data and quantitative data collected through published articles in national and international journals to assess epidemiology and its way forward to prevent NCDs in the Nepali Army. Nepali Army policymakers and the Nepali Army Medical Corps need to understand the growing burden of NCDs among soldiers and implement targeted strategies to protect their health and avoid premature mortality in the Nepali Army.